Uncovering the Potential of a Circular Economy from an Islamic Economic Perspective - Hidayat, Muhammad Syahrul (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
This research reveals the potential of a circular economy from an Islamic economic perspective to integrate circular economic concepts that focus on the wise use of resources and reduce waste with Islamic economic principles that emphasize social justice, sustainability, and economic balance. In this research, a literature analysis and comparative study were carried out on the concept of a circular economy and the principles of Islamic economics. This research was conducted to fill existing research gaps and provide new insights into developing a sustainable economy following Islamic religious principles. The research results show a high compatibility between the circular economy and the Islamic economy. The circular economy concept which involves recycling practices, product reuse, and waste reduction is in harmony with Islamic economic principles which emphasize distributive justice, community empowerment, and environmental protection. These findings can be used as a practical guide for economic practitioners, government, and society in adopting and implementing a circular economy in the context of an Islamic economy.